Effect of Highbush blueberry consumption on markers of metabolic syndrome : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Nutritional Science at Massey University, Palmerston North, New Zealand - Pranprawit, Araya (Massey University, 2014)
Background : Metabolic syndrome (MS) is becoming a major public health challenge worldwide, and is associated with a higher risk of the development of several chronic diseases including type II diabetes. Being physically active would provide the most effective management for metabolic disorders; however, the use of dietary bioactive compounds from various plants has also been proposed as an alternative approach. A number of experimental studies indicate that Lowbush blueberries may be able to reduce symptoms of MS but the evidence for Highbush blueberries, which are commonly consumed, is scarce and their benefits remain doubtful. Therefore, the primary objective of this thesis was to investigate the effect of selected Highbush blueberries grown in New Zealand on their potential for managing metabolic-related disorders in order to provide further knowledge of the role for bioactive compounds from Highbush blueberries. Method : The selected eight Highbush blueberry cultivars were initially characterised by measuring total phenolic content using a Folin-Ciocalteu procedure; anthocyanin profiles and chlorogenic acid concentration by HPLC; and antioxidant capacity by the ferric reducing antioxidant power (FRAP) and by 2,2, diphenyl-picrylhydrazyl (DPPH) assays (Chapter 3). Further experiments were then carried out to investigate whether these Highbush blueberries possess any activity against measures of MS in vitro. The ability of Highbush blueberries to inhibit α-amylase and α-glucosidase, the enzymes involved in breaking down starch, and their abilities to enhance the growth of beneficial probiotic bacteria, another mechanism associated with improving insulin resistance, were tested in Chapter 4. Finally, the physiological effects of Highbush blueberry consumption on metabolic syndrome biomarkers were assessed in vivo using animal models of diet-induced metabolic syndrome (Chapter 5-7). Results : Our results demonstrated that selected Highbush blueberries grown in New Zealand contained considerable amounts of polyphenolics and total anthocyanins, and exhibited high antioxidant activities, with ‘Burlington’ and ‘Elliott’ cultivars exhibiting the highest total phenolic content (> 3.4 mg GAE/g frozen berries (FB)), total anthocyanins (> 2.2 mg/g FB) and antioxidant capacities (FRAP; > 3.0 mg FeSO4/g FB, DPPH; > 65% inhibition at 5 mg FB). Further in vitro experiments supported the ability of these blueberries to inhibit α-amylase (10-40% inhibition at 20 mg FB) and α-glucosidase (10-50% inhibition at 25 mg FB); additionally, some blueberry cultivars possessed the ability to increase the growth of the probiotic bacteria Lactobaccillus acidophilus by more than 0.5 log10 CFU/mL. However, the extent of these benefits was not closely correlated with total phenolic content (R2 < 0.27), total anthocyanins (R2 < 0.23), or antioxidant capacities (FRAP; R2 < 0.42, DPPH; R2 < 0.24) across all genotypes, indicating that these anti-metabolic syndrome abilities were not simply due to the total bioactives or antioxidant capacities presented in the berries. ‘Burlington’ and ‘Bluecrop’, which exhibited strong enzyme inhibition as well as enhanced beneficial probiotic bacterial growth but contained different components of individual anthocyanins, were chosen for further testing in vivo. Rats fed a high-fat-high-sugar diet plus 1% freeze-dried whole blueberries (both cultivars) for 8 weeks showed signs of improvement of glucose tolerance and exhibited between 30 and 36% decrease in the degree of insulin resistance (HOMA-IR) as compared to the controls. The blueberries also showed a trend to increase the growth of beneficial bacteria, Lactobacillus spp. (P = 0.20) and Bifidobacterium spp. (P = 0.15), in the rats’ caecal content. However, no reduction in body weight or fat accumulation was observed with blueberry supplementation. There were no significant differences (P > 0.05) in the abilities of ‘Burlington’ and ‘Bluecrop’ to modulate any metabolic biomarkers assessed in vivo. Conclusion : Inclusion of the blueberries into the diet showed promise for management of some markers of metabolic syndrome, in particular the improvement of insulin sensitivity and glucose tolerance. The results of these studies shed some light on the beneficial effect of selected NZ Highbush blueberries against insulin resistance associated with metabolic syndrome.
Keywords: Highbush blueberries; Vaccinium corymbosum; Metabolic syndrome; Blueberry analysis; Blueberry physiology; Insulin resistance; Det experimentation on rats